2017
DOI: 10.1080/10641955.2016.1273363
|View full text |Cite
|
Sign up to set email alerts
|

Placental expression of sFlt-1 and PlGF in early preeclampsia vs. early IUGR vs. age-matched healthy pregnancies

Abstract: High sFlt-1 concentrations may account for diminished maternal serum PlGF levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
5
20
0
2
Order By: Relevance
“…In-depth analyses of the differences in FGR placenta that revealed candidate genes and pathways that fit previously reported histopathological and protein data. For example, we found hyperacetylation and higher mRNA of the sFlt-1 region in FGR placentas, consistent with studies reporting upregulation of sFlt-1 protein in FGR placentas [ 36 , 37 ]. Furthermore, sFlt-1 is known to be enriched in syncytial knots, which are also observed in FGR placenta [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…In-depth analyses of the differences in FGR placenta that revealed candidate genes and pathways that fit previously reported histopathological and protein data. For example, we found hyperacetylation and higher mRNA of the sFlt-1 region in FGR placentas, consistent with studies reporting upregulation of sFlt-1 protein in FGR placentas [ 36 , 37 ]. Furthermore, sFlt-1 is known to be enriched in syncytial knots, which are also observed in FGR placenta [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, exposure to PFOS, PFOA, and HFPO‐DA resulted in decreased expression of all four of the proliferation markers measured, although this trend was significant only in the case of PLGF in SFM. This is of particular interest because expression PLGF , which regulates trophoblast proliferation as well as angiogenesis, has been shown in both maternal serum and placenta to be inversely associated with preeclampsia 43,44 . In addition, pro‐apoptotic markers BAD and BAX were up‐regulated and anti‐apoptotic BCL2 was down‐regulated in both SFM and SSM after exposure to PFOA, PFOS, or HFPO‐DA.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PlGF is postulated to be lowered due to suppression by persistent placental hypoxia resulting from an underdeveloped utero-placental circulation. However, studies have also shown increased 3 or no change in PlGF expression 22 in pre-eclamptic placental tissue. Regulation of PlGF expression is unclear, but several mechanisms have been explored such as endoplasmic reticulum stress and epigenetic changes altering the effect of the transcription factor hypoxia-inducible factor-1α (HIF1-α), although the role of HIF1-α in trophoblast growth is debated.…”
Section: Plgf In Pre-eclampsiamentioning
confidence: 99%